How to characterize a Digital Twin: A Usage-Driven Classification. Issue 1 (2021) - Julien, N.; Martin, E.
Abstract: Last years, publications on the Digital Twin have been increasing sharply without any real coherence, representing very different realities. In order to clarify its scope, we propose not only a global definition, but also a complete, usage-driven classification methodology. This enables to integrate data and models as well as applications in a generic overview. Moreover, the usage-driven deployment of the Digital Twin allows to be user-centric, in order to foster acceptance. We give various examples of the interest of this classification to support the deployment of the Digital Twin in all industrial applications.